Respuesta :

Step 1

Write the additive property of addition.

[tex](a+b)+c=\text{ a+(b+c)}[/tex]

Where

[tex]\begin{gathered} a=\text{ -1} \\ b=2.8 \\ c=-2 \end{gathered}[/tex]

Step 2

Find the simplified form of the problem using the property in step 1

[tex](-1+2.8)+(-2)=-1+(2.8+(-2))[/tex][tex]\begin{gathered} 1.8-2=-1+0.8 \\ -0.2=-0.2 \end{gathered}[/tex]

Hence the rewritten form of the problem using the additive property is

(-1+2.8)+(-2) and the simplified form of the problem = -0.2

ACCESS MORE